Numerical and experimental study of the weld joints formation in welding foam materials; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Bezginov R. O. Roman; Krektuleva R. A. Raisa Alekseevna; Mishin M. A. Mikhail; Cherepanov O. I. Oleg; Cherepanov R. O. Roman (2014, 2014)
Title screen